Exploring Islam’s Contribution to Human Rights: A Critical Review of “Islam and Human Rights: With Special Reference to Qur’anic Perspective - Reddy, Sawaithapa (International Journal of Advanced Research in Peace, Harmony and Education; Vol 8 No 2 (2023): International Journal of Advance Research in Peace, Harmony and Education, 2023)
This review critically evaluates the article “Islam and Human Rights: With Special Reference to Qur’anic Perspective,” which examines the compatibility of Islam, as derived from the Qur’an, with fundamental human rights principles. The central thesis posits that the Qur’an provides a comprehensive framework that aligns with contemporary international standards, emphasizing principles such as human dignity, equality, and justice. While the essay makes a compelling argument, this review acknowledges certain challenges, including potential oversimplification of Islamic jurisprudence and the need for a more nuanced exploration of cultural and regional variations within the Muslim world. Despite these critiques, the review underscores the significance of fostering a nuanced dialogue on Islam and human rights and encourages further research to advance our understanding of the relationship between Islamic teachings and the promotion of human rights globally.